Business Model Innovation in the Era of Digital Transformation - Srisuwan, Nattapong; Phromphisute, Kanya (ICON Publisher, 2025)
This study presents a systematic literature review (SLR) that explores the dynamic interplay between Business Model Innovation (BMI) and Digital Transformation (DT). Drawing on a curated selection of 11 peer-reviewed articles published in leading journals, this review identifies theoretical foundations, methodological patterns, and thematic trends that shape current scholarship at the intersection of BMI and DT. The findings reveal that digital transformation acts as a strategic catalyst that compels firms to reconfigure value creation, delivery, and capture mechanisms, leading to novel business model configurations. Three dominant BMI pathways in digital contexts are identified: enhancement of existing models, extension through digital platforms, and disruptive creation of entirely new value logics. The literature demonstrates a strong reliance on theoretical frameworks such as Dynamic Capabilities Theory and the Resource-Based View, yet remains methodologically fragmented, with a predominance of qualitative case studies and a lack of longitudinal or cross-sector analyses. Notable research gaps include the need for empirical studies in developing economies, robust measurement frameworks for digital BMI, and greater integration of ecosystem-oriented perspectives. This study contributes to the consolidation of fragmented insights and proposes a future research agenda that emphasizes multi-level analysis, theoretical integration, and methodological diversification. The review offers both scholarly direction and practical relevance for organizations navigating digital transformation through business model innovation.